The Extra-Membranous Domains of the Competence Protein HofQ Show DNA Binding, Flexibility and a Shared Fold with Type I KH Domains - Tarry M; Jääskeläinen M; Paino A; Tuominen H; Ihalin R; Högbom M (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2022)
Secretins form large oligomeric assemblies in the membrane that control both macromolecular secretion and uptake. Several Pasteurellaceae are naturally competent for transformation, but the mechanism for DNA assimilation is largely unknown. In Haemophilus influenzae, the secretin ComE has been demonstrated to be essential for DNA uptake. In closely related Aggregatibacter actinomycetemcomitans, an opportunistic pathogen in periodontitis, the ComE homolog HofQ is believed to be the outer membrane DNA translocase. Here, we report the structure of the extramembranous domains of HofQ at 2.3 å resolution by X-ray crystallography. We also show that the extra-membranous domains of HofQ are capable of DNA binding. The structure reveals two secretin-like folds, the first of which is formed by means of a domain swap. The second domain displays extensive structural similarity to K homology (KH) domains, including the presence of a GxxG motif, which is essential for the nucleotide-binding function of KH domains, suggesting a possible mechanism for DNA binding by HofQ. The data indicate a direct involvement in DNA acquisition and provide insight into the molecular basis for natural competence.